Implementasi Reformasi Organisasi Perizinan Di Dinas Perizinan Kota Yogyakarta - Muallidin, Isnaini (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2012)
This paper aims to review the implementation of the reform of the licensing organization in an effort to improve the quality of public services in Dinas Perizinan of the Yogyakarta city. It focuses on three aspects, namely: formalization, centralization, and specialization. This paper revealed that the level of formalization in Dinas Perizinan is influenced by the dynamics of socio-economic conditions and some regulation-related issues. On the aspect of specialization there are problems related to the insufficient number as well as competence of the staffs. Progress has been made in the presence of an intense coordination system to assure the responsiveness and accuracy of the service.